2021
DOI: 10.1126/sciadv.abd9117
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired mechano-photonic artificial synapse based on graphene/MoS 2 heterostructure

Abstract: Developing multifunctional and diversified artificial neural systems to integrate multimodal plasticity, memory, and supervised learning functions is an important task toward the emulation of neuromorphic computation. Here, we present a bioinspired mechano-photonic artificial synapse with synergistic mechanical and optical plasticity. The artificial synapse is composed of an optoelectronic transistor based on graphene/MoS2 heterostructure and an integrated triboelectric nanogenerator. By controlling the charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(146 citation statements)
references
References 55 publications
0
134
0
Order By: Relevance
“…[ 248–257 ] Further developing sophisticated artificial sensory synapses is of great significance to neuromorphic interface of neurorobots, future self‐powered electronic skin, human–computer interaction, artificial intelligence, etc. [ 258,259 ] Sun's group developed a piezoelectric graphene artificial sensory synapse by coupling PENG with an electrical double layer transistor. [ 260 ] Piezoelectric potential from PENG could effectively power the synaptic device.…”
Section: Applications In Self‐powered Active Sensorsmentioning
confidence: 99%
“…[ 248–257 ] Further developing sophisticated artificial sensory synapses is of great significance to neuromorphic interface of neurorobots, future self‐powered electronic skin, human–computer interaction, artificial intelligence, etc. [ 258,259 ] Sun's group developed a piezoelectric graphene artificial sensory synapse by coupling PENG with an electrical double layer transistor. [ 260 ] Piezoelectric potential from PENG could effectively power the synaptic device.…”
Section: Applications In Self‐powered Active Sensorsmentioning
confidence: 99%
“…In order to mimic a more practical and complex nervous system, it has been reported that the triboelectric potential as the gate voltage of the optoelectronic synaptic transistor can cooperate with mechanical and optical stimulation to achieve the multimodal plasticity. Figure 8 a shows a mechano-photonic synapse device that can synergize mechanical and optical stimulation, which is composed of a TENG and a graphene/MoS 2 heterostructure transistor [ 91 ]. The integrated TENG uses a vertical contact-separation mode, in which the Cu electrode acts as a movable friction layer, and the PTFE/Cu friction layer is integrated on the transistor to provide different gate voltages by changing the mechanical displacement.…”
Section: Tengs As Tactile Stimulators For Artificial Synapsesmentioning
confidence: 99%
“…( d ) Functional relationship between numbers of training samples and recognition accuracy. Reproduced with permission [ 91 ]. Copyright 2021, American Association for the Advancement of Science.…”
Section: Figurementioning
confidence: 99%
“…Similarities between biological structures and artificial neural-like networks have inspired the development of neuron-based mechanical sensing and optical sensing [9][10][11]. The olfactory neurons that exist in the olfactory bulb of higher animals play a key role in extracting olfactory signals through gas sensing [12].…”
Section: Introductionmentioning
confidence: 99%